A Dairy Herd Case Investigation with Very Low Dietary Cation–Anion Difference in Prepartum Dairy Cows - Melendez, Pedro; Poock, Scott (Frontiers in Nutrition, 2017)
During the periparturient period, subclinical hypocalcemia (Total plasma Ca concentration < 2.0 mmol/l) is a potential problem for the dairy cow; consequently its prevention is essential for success of fertility and productive performance. Dietary cation-anion difference (DCAD) has been defined as the difference in milliequivalents of cations (Na, K) and anions (Cl, S) per kilogram of dry matter (DM) and has a direct impact on blood acid-base metabolism. Diets rich in K and Na induce metabolic alkalosis, interfering with tissue sensitivity to parathyroid hormone (PTH), and diets rich in Cl and S (anionic salts) cause metabolic acidosis, reducing the risk of hypocalcemia. Consequently, the use of anionic salts has become a popular method to prevent hypocalcemia in dairy cattle. Monitoring diets with anionic salts can be done by measuring urine pH, with optimal values between 6.2 and 6.8 for Holstein cows. The objective of this report is to present a herd case investigation involving a dairy farm feeding a very low DCAD (- 143 mEq/kg DM), expecting improved Ca homeostasis. The diet of -143 mEq/kg (urine pH 5.2 to 5.8) was changed to a diet with -53 mEq/kg DM (urine pH 6.2-6.8). Blood samples were taken at the time of calving for 10 cows that calved before and then for 10 cows that calved after changing the diet. Cows with extremely low DCAD had Ca concentrations of 2.11±0.22 mmol/l and cows with a more moderated DCAD, 2.11±0.16 mmol/l (P > 0.05). Several other blood metabolites (P, Mg, Na, K, Cl, albumin, globulins, blood urea nitrogen, creatinine and GGT) were also similar between groups. This very low DCAD during the prepartum period may severely compromise animal physiology unnecessarily, with little advantage over normal calcium concentrations at parturition, when compared with a less negative DCAD (- 53 mEq/kg DM). Feeding a less negative DCAD ration (-53 mEq/kg DM) did not decrease plasma Ca levels right after parturition compared to a DCAD ration of -143 mEq/kg DM, reinforcing the lack of benefit of a more negative DCAD.